Characterization of a Zika Virus Isolate from Colombia. - Anismrita Lahon; Ravi P Arya; Alexander R Kneubehl; Megan B Vogt; Natalie J M Dailey Garnes; Rebecca Rico-Hesse (Public Library of Science (PLoS), 2016)
Zika virus (Flavivirus genus) is the first mosquito-borne virus known to cause high rates of microcephaly and abortion in humans. Typically, Zika virus causes a self-limiting, systemic illness; however, the current outbreak of Zika virus in the Americas has been associated with increased rates of fetal malformations and Guillain-Barré syndrome. Very few Zika virus isolates have been described in the literature, and live viruses are needed to perform studies of pathogenesis and to develop vaccines and treatments.We isolated Zika virus, strain FLR, directly from the serum of an individual infected in Barranquilla, Colombia (December, 2015). Here, we describe the patient's clinical course and characterize strain FLR by its growth characteristics in mosquito and mammalian cells and its partial resistance to UV-inactivation. The full genome sequence of FLR was also analyzed (including the 3' un-translated region), to determine its probable geographic origin, and to pinpoint structural differences from other Zika virus strains.We anticipate that the study of this low passage, clinical isolate of Zika virus, which is available for worldwide distribution, will help uncover the mechanisms of viral replication and host immune responses contributing to the varied and sometimes severe clinical presentations seen during the current epidemic in the Americas.